2013
DOI: 10.1017/sjp.2013.94
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Sociocultural Attitudes Towards Appearance Questionnaire-3 among Brazilian Young Adults

Abstract: The objective was evaluating the psychometric properties of the Sociocultural Attitudes Towards Appearance Questionnaire-3 (SATAQ-3) among Brazilian young adults of both genders. The sample was composed by 506 undergraduate students (295 females and 211 males), aged between 17 and 29 years old. Exploratory and confirmatory factor analyses were used for construct validity (N = 506). Correlations between the SATAQ-3 scores and those of the Tripartite Influence Scale (TIS) and Body Shape Questionnaire (BSQ) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 45 publications
4
22
0
6
Order By: Relevance
“…In both satisfied (BSQ <80) and dissatisfied groups (BSQ ≥ 80), the findings showed acceptable adherence rates. Moreover, the results indicated factorial loads above 0.3 for all items and confirmed that the factor structure of SATAQ-3 in female track and field athletes was identical to that found by Amaral et al 16 . Therefore, the factor structure of SATAQ-3 was as follows: "Overall Internalization" (items 4, 7, 8, 11, 15, 16 and 20), "Information" (items 1, 5, 17, 21, 25 and 29 ), "Pressure" (items 2, 10, 14, 18, 22 and 26), "Athletic Internalization" (Items 19, 23, 24 and 30) and "Reverse score questions" (items 3, 6, 9, 12 13, 27 and 28).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In both satisfied (BSQ <80) and dissatisfied groups (BSQ ≥ 80), the findings showed acceptable adherence rates. Moreover, the results indicated factorial loads above 0.3 for all items and confirmed that the factor structure of SATAQ-3 in female track and field athletes was identical to that found by Amaral et al 16 . Therefore, the factor structure of SATAQ-3 was as follows: "Overall Internalization" (items 4, 7, 8, 11, 15, 16 and 20), "Information" (items 1, 5, 17, 21, 25 and 29 ), "Pressure" (items 2, 10, 14, 18, 22 and 26), "Athletic Internalization" (Items 19, 23, 24 and 30) and "Reverse score questions" (items 3, 6, 9, 12 13, 27 and 28).…”
Section: Resultssupporting
confidence: 87%
“…However, for the present investiga-tion, only "Overall Internalization" and "Athletic Internalization" subscales were used, totaling fourteen items. The SATAQ-3 version used in this study was translated and adapted for the young Brazilian population 15 , with content and construct validity and reproducibility and reliability attested to this population 16 . For this sample, internal consistency was calculated by Cronbach's alpha, with satisfactory values of 0.82 and 0.85 for "Overall Internalization" and "Athletic Internalization" subscales, respectively.…”
Section: Instrumentsmentioning
confidence: 99%
“…The SATAQ-3 has four factors: General internalization (e.g., "I would like my body to look like the people who are on TV"), Athletic internalization (e.g., "I compare my body to that of people who are athletic"), Pressure (e.g., "I've felt pressure from TV or magazines to look pretty") and Information (e.g., "TV programs are an important source of information about fashion and being attractive"). The version validated for use with young Brazilian men was used, which has been shown to have appropriate psychometric qualities (Amaral, Ribeiro, Conti, Ferreira, & Ferreira, 2013). Only two factors were used: General internalization and Athletic internalization.…”
Section: Methodsmentioning
confidence: 99%
“…Since it is a sport in which body is in focus, aesthetic standards of thinness and low body fat are required from athletes -as the standard propagated by the media [4][5][6] , which can affect the body image of these athletes 3 . This construct is defined as the mental representation of the own body and is related to social, emotional, physiological factors and also to the environment in which the individual is inserted 7 .…”
Section: Introductionmentioning
confidence: 99%
“…This questionnaire has been validated for the Brazilian university population 4 . The instrument has already been assessed for the Brazilian adolescent population, showing good indicators of validity and reliability 5 and has not undergone changes for this population.…”
mentioning
confidence: 99%